Settlement choice under conditions of rapid shoreline displacement in Wemindji Cree Territory, subarctic Quebec. (30th May 2020) - Wren, Colin D.; Costopoulos, Andre; Hawley, Maclean
Abstract: We show that known archaeological sites in the Wemindji area of central eastern James Bay in Canada are more likely to show higher shoreline stability within a 2 km radius than randomly selected locations. We show that archaeological sites are surrounded by areas of greater diversity in shoreline stability within a 20 km radius than random locations. We propose that a cultural algorithm guides the selection of occupation sites in the region, including by today's Cree occupants, which identifies islands of stability in a sea of change in order to minimize the need for residential mobility while maximizing the diversity of resources available through logistical trips. This algorithm favours residential stability and logistical mobility, and evolved in the context of rapid shoreline displacement caused by post-glacial isostatic land-uplift.